2023
DOI: 10.3390/ijerph20054105
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Histological Structure of Adrenal Glands and Corticosterone Level after Whey Protein or Bee Pollen Supplementation in Running and Non-Running Rats

Abstract: Due to the many health-promoting properties of bee pollen and whey protein, both products are widely used as dietary supplements. According to these reports on their health-promoting properties, the aim of our study is to assess whether these products can influence the structure and function of the adrenal glands in rats. Thirty male Wistar rats were divided into six equal groups. Among them, there were three groups which included non-running rats and three groups which included running rats. Both of these run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
1
0
0
Order By: Relevance
“…The present study illustrated that propolis administration resulted in many histological and ultrastructural improvements in the adrenal gland of rat fetuses and pups. This is in line with the findings of Frankowska et al (2023) who found that bee pollen supplementation decreased the pyknotic nuclei, decreased collagen fibers and improved the histology of adrenal gland in rats. Similarly, Bruno (2005) showed that bee products contain high levels of vitamin B5 that is very beneficial for adrenal glands during stress.…”
Section: Discussionsupporting
confidence: 92%
“…The present study illustrated that propolis administration resulted in many histological and ultrastructural improvements in the adrenal gland of rat fetuses and pups. This is in line with the findings of Frankowska et al (2023) who found that bee pollen supplementation decreased the pyknotic nuclei, decreased collagen fibers and improved the histology of adrenal gland in rats. Similarly, Bruno (2005) showed that bee products contain high levels of vitamin B5 that is very beneficial for adrenal glands during stress.…”
Section: Discussionsupporting
confidence: 92%